2015
DOI: 10.1016/j.cretres.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Response and recovery of the Comanche carbonate platform surrounding multiple Cretaceous oceanic anoxic events, northern Gulf of Mexico

Abstract: a b s t r a c tThe ubiquity of carbonate platforms throughout the Cretaceous Period is recognized as a product of high eustatic sea-level and a distinct climatic optimum induced by rapid sea-floor spreading and elevated levels of atmospheric carbon-dioxide. Notably, a series of global oceanic anoxic events (OAEs) punctuate this time-interval and mark periods of significantly reduced free oxygen in the world's oceans. The best records of these events are often from one-dimensional shelf or basin sections where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 92 publications
2
34
1
Order By: Relevance
“…Tiskatine NC7A: The LAD of M. hoschulzii has been conventionally calibrated (Bralower et al, 1993; Ogg and Hinnov, 2012) to a position slightly above the base of the upper Aptian, at a level close to the base of the E. martini Zone (SMAS). This conventional calibration for the top NC7A appears depressed to more recent records from northwestern Europe (Jeremiah, 2000(Jeremiah, , 2001, the Gulf of Mexico (Phelps et al, 2015; Supplementary document) and this study at Tiskatine (EAB). Here at Tiskatine M. hoschulzii ranges up to the local "Hypacanthoplites" spp.…”
Section: Age Interpretation Calcareous Nannofossilscontrasting
confidence: 59%
See 1 more Smart Citation
“…Tiskatine NC7A: The LAD of M. hoschulzii has been conventionally calibrated (Bralower et al, 1993; Ogg and Hinnov, 2012) to a position slightly above the base of the upper Aptian, at a level close to the base of the E. martini Zone (SMAS). This conventional calibration for the top NC7A appears depressed to more recent records from northwestern Europe (Jeremiah, 2000(Jeremiah, , 2001, the Gulf of Mexico (Phelps et al, 2015; Supplementary document) and this study at Tiskatine (EAB). Here at Tiskatine M. hoschulzii ranges up to the local "Hypacanthoplites" spp.…”
Section: Age Interpretation Calcareous Nannofossilscontrasting
confidence: 59%
“…Its true LAD is more sporadic, with rare occurrences ranging up into the lowermost Albian of the North Sea (Jeremiah, 2001). Recent studies (Phelps et al, 2015;supplementary document) have shown a more extensive geographical distribution outside of the North Sea. At Tiskatine the acme of C. bosunensis is at bed MTTK 239 (Fig.…”
Section: Age Interpretation Calcareous Nannofossilsmentioning
confidence: 99%
“…Farther south, the Cenomanian‐Turonian Eagle Ford Shale of Texas is probably the best studied OAE2 interval in the Gulf of Mexico region (Corbett & Watkins, ; Corbett, Watkins, & Popspichal, ; Denne and Breyer, ; Denne et al, , ; Dodsworth, ; Donovan et al, ; Eldrett, Minisini, & Bergman, ; Eldrett et al, ; Frush & Eicher, ; Lowery & Leckie, ; Lowery et al, ; Lundquist, ; Pessagno, ; Phelps et al, ). Like in the Western Interior, the pre‐OAE2 sedimentary rocks of Texas are enriched in total organic carbon (TOC) up to ~9 wt % (Hentz & Ruppel, ) and contain proxy evidence for seafloor anoxia, including a lack of benthic foraminifera, absence of bioturbation, and enrichment in certain redox sensitive trace metals (e.g., Denne et al, ; Denne & Breyer, ; Donovan et al, ; Eldrett et al, , ; Lowery et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Frizzell (1954, p. 76), reported that in Texas, C. texanus ranges upward from the Glen Rose Limestone of the Trinity Group into the progressively younger Walnut Clay, Comanche Peak Limestone, and Goodland Limestone of the Fredericksburg Group". Phelps et al (2015) indicated that this species ranges from the mid-to-upper Albian from west Texas. In Mexico, C. texanus has been reported by Scott and González-León (1991) (Figure 5a), which was defined by Vanderpool (1933) from the mid-Albian Comanchean "formation" in southern Oklahoma, later placed in the genus Buccicrenata by Loeblich and Tappan (1949).…”
Section: Foraminiferal Assemblage and Agementioning
confidence: 99%
“…Maync (1955a) recorded the species in the Lower Cretaceous (Guácharo limestone) of eastern Venezuela and prepared a detailed description. Dictyoconus walnutensis is widespread in the Gulf of Mexico region and has been regarded as a stratigraphic marker restricted to the mid-Albian (Douglass, 1960;Maync, 1955a;Bonet, 1956;Scott, 1990;Scott and González-León, 1991;Buitrón et al, 1995;Omaña and Alencaster, 2001;Monreal and Longoria, 1999;Fourcade et al, 1999;Waite et al, 2007); however, it could have ranged to the early late Albian (Phelps et al, 2015). In North Texas this species ranges to the top of Goodland Formation in which the basal upper Albian ammonite Dipoloceras cristatum occurs; so D. walnutensis ranges into basal upper Albian (written communication Scott, 2016).…”
Section: Foraminiferal Assemblage and Agementioning
confidence: 99%